Incidence of shoulder dislocations in the UK, 1995–2015: a population-based cohort study - Gary S Collins; Sarah E Lamb; Sally Hopewell; Daniel Prieto-Alhambra; Andrew Judge; Amar Rangan; Andrew J Carr; Jonathan L Rees; Nigel K Arden; Katherine Edwards; Tim A Holt; Anjali Shah; et al. (BMJ Open)
Objective This cohort study evaluates the unknown age-specific and gender-specific incidence of primary shoulder dislocations in the UK.Setting UK primary care data from the Clinical Practice Research Datalink (CPRD) were used to identify patients aged 16–70 years with a shoulder dislocation during 1995–2015. Coding of primary shoulder dislocations was validated using the CPRD general practitioner questionnaire service.Participants A cohort of 16 763 patients with shoulder dislocation aged 16–70 years during 1995–2015 were identified.Primary outcome measure Incidence rates per 100 000 person-years and 95% CIs were calculated.Results Correct coding of shoulder dislocation within CPRD was 89% (95% CI 83% to 95%), and confirmation that the dislocation was a ‘primary’ was 76% (95% CI 67% to 85%). Seventy-two percent of shoulder dislocations occurred in men. The overall incidence rate in men was 40.4 per 100 000 person-years (95% CI 40.4 to 40.4), and in women was 15.5 per 100 000 person-years (95% CI 15.5 to 15.5). The highest incidence was observed in men aged 16–20 years (80.5 per 100 000 person-years; 95% CI 80.5 to 80.6). Incidence in women increased with age to a peak of 28.6 per 100 000 person-years among those aged 61–70 years.Conclusions This is the first time the incidence of shoulder dislocations has been studied using primary care data from a national database, and the first time the results for the UK have been produced. While most primary dislocations occurred in young men, an unexpected finding was that the incidence increased in women aged over 50 years, but not in men. The reasons for this are unknown. Further work is commissioned by the National Institute for Health Research to examine treatments and predictors for recurrent shoulder dislocation.Study registration The design of this study was approved by the Independent Scientific Advisory Committee (15_260) for the Medicines & Healthcare products Regulatory Agency.